A Fragile Frontier: Fishing in Pekalongan during the Nineteenth Century - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Keywords: Fragile Frontier Fishing in Pekalongan, 19th Century